2017
DOI: 10.1111/jnc.14033
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying protective effects of quercetin against mitochondrial dysfunction and progressive dopaminergic neurodegeneration in cell culture and MitoPark transgenic mouse models of Parkinson's Disease

Abstract: Quercetin, one of the major flavonoids in plants, has been recently reported to have neuroprotective effects against neurodegenerative processes. However, since the molecular signaling mechanisms governing these effects are not well clarified, we evaluated quercetin’s effect on the neuroprotective signaling events in dopaminergic neuronal models and further tested its efficacy in the MitoPark transgenic mouse model of Parkinson’s disease (PD). Western blotting analysis revealed that quercetin significantly ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(85 citation statements)
references
References 100 publications
(197 reference statements)
0
83
0
2
Order By: Relevance
“…In a model of hypobaric-hypoxic brain injury in vivo, QCT prevented cognitive deterioration through SIRT1 upregulation and consequent activation of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1-α), one of the master regulators of mitochondrial biogenesis [ 23 ]. Further, in an in vitro model of dopaminergic neuronal death induced by 6-hydroxydopamine and MitoPark, QCT prevented neuronal death through the activation of the protein kinase D/cAMP response element binding protein/PGC1-α axis, which led to the augmentation of mitochondrial biogenesis and function [ 54 ]. These studies suggest that QCT may exert its beneficial effects ultimately improving neuronal energetic state irrespective of its molecular targets.…”
Section: Discussionmentioning
confidence: 99%
“…In a model of hypobaric-hypoxic brain injury in vivo, QCT prevented cognitive deterioration through SIRT1 upregulation and consequent activation of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1-α), one of the master regulators of mitochondrial biogenesis [ 23 ]. Further, in an in vitro model of dopaminergic neuronal death induced by 6-hydroxydopamine and MitoPark, QCT prevented neuronal death through the activation of the protein kinase D/cAMP response element binding protein/PGC1-α axis, which led to the augmentation of mitochondrial biogenesis and function [ 54 ]. These studies suggest that QCT may exert its beneficial effects ultimately improving neuronal energetic state irrespective of its molecular targets.…”
Section: Discussionmentioning
confidence: 99%
“…A study using drug screening in Caenorhabditis elegans nematodes with neuronal expression of human exon-1 huntingtin (128Q) and mutant Htt striatal cells derived from knock-in HD mice, concluded that isoquercetin improved motor functions in acute spinal cord injury, reduced α-synuclein fibrillization, reduced hippocampal neuronal cell death, improved synaptic plasticity, and reversed histopathological hallmarks of AD [112]. Quercetin also protects against mitochondrial dysfunction and progressive dopaminergic neurodegeneration by activating PKD1-Akt cell survival signaling axis Cell Culture and MitoPark transgenic mouse models of Parkinson's disease [113].…”
Section: Neuroprotective Efficacy Of Quercetinmentioning
confidence: 99%
“…In accordance with these findings, another study showed that the administration of quercetin reduced ROS production, increased mitochondrial manganese-dependent superoxide dismutase (MnSOD) activity and the ratio of B-cell CLL/lymphoma 2 (BCL-2) to BCL2 associated X (BAX) in aluminum-induced oxidative stress rat model (Sharma et al, 2016). Prasad et al (2013) (Ay et al, 2017).…”
Section: Quercetinmentioning
confidence: 60%